Using the information inequity framework to study GenAI equity: analysis of educational perspectives - Sarah Zipf; Chuhao Wu; Tiffany Petricini (Information Research: An International Electronic Journal)
Introduction. Generative AI presents opportunities and challenges for higher education, particularly concerning equity. Understanding stakeholders' perceptions of equity is crucial as AI increasingly influences teaching, learning, and administrative practices.